The Church of Holy Mother of God Zahumska near Ohrid: Retrospective Trends in the Late Byzantine Architecture - Zavorina, Maria L. (Actual Problems of Theory and History of Art, 2022)
In this article, a detailed stylistic analysis of the architectural design of the Church of the Holy Mother Zahumska (1361) is supplemented by a contextual analysis using the available data on the ecclesiastical and political history of the Ohrid Archbishopric and of Serbia of the 14th century. On the basis of the results obtained, it is suggested that the Church is an example of a purposeful appeal to the significant Early Palaeologan monuments of Ohrid, belonging to the architectural tradition of Epirus — namely, to the Church of the Virgin Peribleptos. It could be caused by the coincident desire of the donators. An attempt to clarify the role and place of the Zahumska Church in the local and regional architectural tradition of the late 13th–14th centuries leads to the conceptual problem of the essence and specific manifestations of retrospective trends in Late Byzantine architecture. They can be traced in the reproduction of earlier solutions and compilability of Late Byzantine architecture, in imitation of significant monuments by quoting their individual elements, and extremely rarely in close repetition of these patterns. In this row, the Church of Holy Mother Zahumska is an interesting example of the reproduction of an early local monument, interpreted in accordance with current stylistic trends. This study is based on the research supported by the Program of Fundamental Research of the Ministry of Construction, Housing and Utilities of the Russian Federation and of the Russian Academy of Architec- ture and Construction Sciences — 2022, research project 1.1.1.2.